Pengaruh Edukasi Animasi Interaktif Tanda Bahaya Kelainan Cairan Ketuban Pada Kehamilan Terhadap Peningkatan Pengetahuan Ibu hamil di Klinik Pratama Annissa Surakarta - Munaaya Fitriyya; Dhina Nur Irfani (Akademi Analis Kesehatan Pekalongan, 2021)
Maternal mortality can be occured during pregnancy, childbirth and puerperium. The causes of maternal mortality include bleeding, hypertension, infections, circulatory system disorders, metabolic disorders, and others. Infection is the biggest cause of maternal mortality. One type of infection is chorioamnionitis. Chorioamnionitis is an acute infection of the amniotic fluid, fetus and chorioamnione membrane caused mainly by bacteria. The advantage of using animation with other media such as images that are static or just text the ability to explain changes in circumstances at any time. So the animation function is intended to clarify the message, so that it is not too verbalist, solve the limitations of space in showing in real that something was originally impossible to see, to attract the interest and attention then strengthen motivation. The purpose of the study was to determine the effect of interactive animation education on danger signs of amniotic fluid abnormalities in pregnancy on increasing knowledge of pregnant women at the Pratama Annissa Surakarta Clinic. Research Methodology: This research is an experimental study with a one-group pre-post test design method. Interactive Animation Education on Danger Signs of Amniotic Fluid Abnormalities in Pregnancy Against Increasing Knowledge of Pregnant Women at the Pratama Annissa Surakarta Clinic using the Wilcoxon test, because this research data does not meet the assumption of normality. Non Probability Sampling technique ( not randomly) with quota sampling method. The population of this study was 10 pregnant women. Results: there is an increase in the knowledge score of pregnant women after education the danger signs of amniotic fluid abnormalities, there are no students who have decreased grades, 10 students have increased their grades and there are no students get a fixed score, which means that Animation Education on The Danger Signs of Amniotic Fluid Abnormalities in Pregnancy has a significant effect on the increasing knowledge of pregnant women, Conclusion: Animation Education on The Danger Signs of Amniotic Fluid Abnormalities in Pregnancy has a significant effect on increasing the knowledgeof hami mothers at the Pratama Annissa Surakarta Clinic